Pronoun System in the Raijua Dialect of the Sabu Language: A Descriptive Study (e-Journal of Linguistics, 2026)
This study investigates the pronoun system of the Raijua dialect of the Sabu Language spoken in Sabu Raijua Regency, East Nusa Tenggara, Indonesia. Pronouns are an essential grammatical category because they not only substitute nouns and noun phrases but also reflect social relationships, cultural identity, and participant involvement in communication. The objectives of this study are to identify the types of pronouns and describe their grammatical and social functions in the Raijua dialect. This research employed a descriptive qualitative design. Data were collected through semi-structured interviews, audio recordings, and documentation involving three native speakers of the Raijua dialect. The collected data were transcribed, classified, and analyzed based on pronoun categories and their functions in discourse. The findings reveal seven categories of pronouns in the Raijua dialect, namely personal pronouns, possessive pronouns, reflexive pronouns, demonstrative pronouns, indefinite pronouns, relative pronouns, and distributive pronouns. The analysis further shows that pronouns perform several important functions, including replacing subjects and objects, expressing possession, distinguishing inclusive and exclusive first-person plural references, and reflecting social relationships among speakers. A distinctive characteristic of the Raijua dialect is the contrast between the inclusive pronoun dii (‘we’, including the listener) and the exclusive pronoun 'jii (‘we’, excluding the listener). This inclusive-exclusive distinction represents a significant typological feature of Austronesian languages and demonstrates how linguistic forms encode social interaction and group membership. Furthermore, pronouns such as dii, 'jii, era, and roo serve as markers of solidarity, cultural identity, kinship, and social boundaries within the Raijua-speaking community. This study contributes to descriptive linguistics, Austronesian language typology, and the documentation and preservation of regional languages in Indonesia
Keywords: Pronoun; Raijuwa Dialect; Sabu Language; Descriptive Linguistics; Austronesian Language